2022
DOI: 10.3390/jcm11030630
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Derived Hemopexin as a Candidate Therapeutic Agent for Acute Vaso-Occlusion in Sickle Cell Disease: Preclinical Evidence

Abstract: People living with sickle cell disease (SCD) face intermittent acute pain episodes due to vaso-occlusion primarily treated palliatively with opioids. Hemolysis of sickle erythrocytes promotes release of heme, which activates inflammatory cell adhesion proteins on endothelial cells and circulating cells, promoting vaso-occlusion. In this study, plasma-derived hemopexin inhibited heme-mediated cellular externalization of P-selectin and von Willebrand factor, and expression of IL-8, VCAM-1, and heme oxygenase-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Administration of plasma-derived hemopexin before or during VOC in the Townes SCD mouse model, triggered either by heme or hypoxia-reoxygenation, have shown that administration of hemopexin can prevent or reduce VOC, but also, have antioxidant and anti-inflammatory effects (46,47). Therefore, an objective became to investigate hemopexin's role in the interplay between factor I and heme.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of plasma-derived hemopexin before or during VOC in the Townes SCD mouse model, triggered either by heme or hypoxia-reoxygenation, have shown that administration of hemopexin can prevent or reduce VOC, but also, have antioxidant and anti-inflammatory effects (46,47). Therefore, an objective became to investigate hemopexin's role in the interplay between factor I and heme.…”
Section: Discussionmentioning
confidence: 99%
“…Autoxidation of HbFe(II)O2 to HbFe(III) enhances heme transfer to lipids 26,[70][71][72] , neutrophils, macrophages, and the vascular endothelium 39 triggering inflammation 73 and cell adhesion pathways 74 that are important contributors to VOC. Murine models of SCA provide proof of concept that haptoglobin and hemopexin prevent, and in part reverse, Hb-and heme-induced vascular stasis 75,76 . Since haptoglobin consumption is very rapid during brisk hemolysis characteristic of human SCA, haptoglobin replacement therapy may be challenging 26,67 .…”
Section: Therapeutic Potential Of Haptoglobin and Hemopexinmentioning
confidence: 96%
“…Hemopexin is a strong haeme-binding protein. 5 Free haeme in SCD is a well known cause of nitric oxide (NO) scavenging. The lack of NO increases the expression of adhesion molecules on endothelial and circulating cells, facilitating vaso-occlusion.…”
Section: Hemopexin Reduces Endothelial Adhesion Of Sickle Erythrocytesmentioning
confidence: 99%